2013
DOI: 10.1189/jlb.1012498
|View full text |Cite
|
Sign up to set email alerts
|

IL-4Rα on CD4+ T cells plays a pathogenic role in respiratory syncytial virus reinfection in mice infected initially as neonates

Abstract: RSV is the major cause of severe bronchiolitis in infants, and severe bronchiolitis as a result of RSV is associated with subsequent asthma development. A biased Th2 immune response is thought to be responsible for neonatal RSV pathogenesis; however, molecular mechanisms remain elusive. Our data demonstrate, for the first time, that IL-4Rα is up-regulated in vitro on human CD4(+) T cells from cord blood following RSV stimulation and in vivo on mouse pulmonary CD4(+) T cells upon reinfection of mice, initially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
63
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 39 publications
3
63
0
1
Order By: Relevance
“…gene in CD4 C T cells abolished hRSV-induced airway AHR and lung damage upon reinfection with hRSV. 87 However, these results are controversial because several reports have shown that CD4 C T cells are required for the clearance of the virus and to promote antibody response against hRSV. 60,[88][89][90] In this sense, it seems that dysregulation of CD4 C T cells promote harmful Th profiles but these cells are still required for hRSV clearance.…”
Section: An Adequate Cd4mentioning
confidence: 99%
See 1 more Smart Citation
“…gene in CD4 C T cells abolished hRSV-induced airway AHR and lung damage upon reinfection with hRSV. 87 However, these results are controversial because several reports have shown that CD4 C T cells are required for the clearance of the virus and to promote antibody response against hRSV. 60,[88][89][90] In this sense, it seems that dysregulation of CD4 C T cells promote harmful Th profiles but these cells are still required for hRSV clearance.…”
Section: An Adequate Cd4mentioning
confidence: 99%
“…86 The pathogenic role of CD4 C T during re-infection with hRSV in adult mice, after being infected as neonates, can be explained by the induction of an exaggerated T H 2 response, demonstrated by the cytokine profile observed in these animals. 87 This could be explained, at least in part, by the upregulation of the IL-4Ra. Specific deletion of the IL-4Ra.…”
Section: An Adequate Cd4mentioning
confidence: 99%
“…Using this model, we have recently demonstrated that interleukin 4 receptor ␣ (IL-4R␣) on Th cells plays a pathogenic role in RSV reinfection-associated immunopathophysiology (4). We showed that neonatal Th cells (i.e., Th1 and Th2 cells) express higher levels of IL-4R␣ than adult Th cells.…”
mentioning
confidence: 94%
“…In this model, neonatal mice (Ͻ7 days old) are infected with RSV and various immunological parameters are measured. Notably, RSV-infected neonates mount limited Th1 (CD3 (4,6,8,9) and multifunctional Th (CD3 ϩ , CD4 ϩ , IFN-␥ ϩ , IL-4 ϩ ) cells (4), while the number of Th1 cells upon reinfection is equivalent to that in mice initially infected as adults. This biased Th2 response observed upon reinfection is associated with enhanced airway hyperreactivity (AHR), airway and lung eosinophilia, and mucus hyperproduction (4,6,8,9), all of which are consistent with the observations for infants from the 1960s clinical trials who died from community-acquired RSV infection (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation